Penerapan Metode Fun Creative Learning dalam Meningkatkan Minat Belajar Siswa - Ariyani, Lia; Syarnubi, Syarnubi; Dewi, Mutia; Septia Fahiroh; Padli (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The method used in this research is quantitative research with an experimental approach, using a one group pretest and post-test design. The population of this study was all students at SD Negeri 2 Kayuara, where the sample was 32 students in class IV B. Data collection techniques use observation, tests, questionnaires and documentation. Data analysis was carried out using the t-test. The results of the research show that the results of data analysis using the t-test on the pre-test data before the fun creative learning method was applied and the post-test data after the fun creative learning method was applied, namely the value of t0 = 9.46 is greater than t0 (both 5% significance level or 1%), 2.04 < 10.70 > 2.74. This means that the alternative hypothesis (Ha):